“Liberating” the Hijab - Mohd. Noor, Noraini (Springer, 2009)
Liberation psychology is beginning to receive interest outside of Latin America and more recently, workers from South Africa and Australasia have identified with this body of theory and practice. Can this orientation be used to consider the issue of hijab (a headscarf or a piece of fabric covering a Muslim woman’s head) which has lately been the subject of much controversy and debate? Though this debate has been going on for quite some time, both in Muslim and non-Muslim countries, it was only after the French government banned hijab and other religious symbols in public schools in 2004 that this issue became the focus of much media hype. We feel the liberation orientation can be used in the discussion of the hijab by placing the decision of the hijab onto the women themselves. However, this issue is complex because as eloquently espoused by Ezekial, hijab is inseparable from and overlaps with a number of other concerns such as racism, ethnocentrism, human rights, religion, feminism, colonialism, politics, economic and social injustice, and others. Thus, it may be difficult to confine the issue of hijab without encroaching upon these related areas. Bearing in mind these difficulties, we will examine the issue of hijab by going beyond the simple piece of cloth to the meanings attributed by people and to the more complex dynamics underlying it.